A study on zoo and wild animal attacks and bites to zookeepers, wildlife rangers and the general public in Malaysia - Azman, Anis Zafirah (2015)
Animal attacks and bites can occur in free range and captivity. Globally, there were many fatal cases reported due to injuries caused by animals. In Malaysia, fatal cases of wild animals attack and bite reported by media are caused by snakes, crocodiles, bears and tigers. Many cases of wild animals attack and bite in Malaysia are unreported. This study is to determine species of wild and zoo animals that attack and bite human in Malaysia. It discusses general management post-incidents and measures to avoid future attacks and bites. Interview sessions were conducted with those who currently work or former staff of Malaysian Zoos and Department of Wildlife and National Parks (DWNP) in Malaysia. Mammals were the highest cases of attacks and bites documented. Most of the victims were male. Majority were hospitalized. All respondents suggested the usage of additional or aiding device while handling animals. There are many more cases of wild and zoo animal attacks and bites that are not being documented. Further research is required to access factors that cause animal attacks and bites and the appropriate medical treatment.